Eicosanoids and Iso-Eicosanoids: Constitutive, Inducible and Transcellular Biosynthesis in Vascular Disease - Maclouf, Jacques; Folco, Giancarlo; Patrono, Carlo (Thrombosis and Haemostasis, 1998)
Current understanding of the mechanisms underlying plaque development (1-3) assigns a key role to oxidative modifications of specific phospholipids that are carried into the subendothelial space with low-density lipoproteins (LDL). These variably oxidized lipids in turn trigger a chronic inflammatory response, largely orchestrated by monocytes/macrophages (1-3). Thrombotic occlusion of a major coronary or cerebral vessel can complicate the sudden fissuring or rupture of a plaque and lead to myocardial infarction or ischemic stroke, respectively. The determinants of lipid oxidation, plaque fragility and of the hemostatic response to plaque rupture, as well as the hemodynamic factors influencing the multifactorial process of atherothrombosis represent targets of pharmacological interventions aimed at reducing the risk of cardiovascular and cerebrovascular complications.The oxidative modifications of the arachidonic acid backbone, that lead to the formation of enzymatic (eicosanoids) and non-enzymatic (iso-eicosanoids) derivatives (Fig. 1), can provide autacoid mechanisms modulating activation of the major cellular players of atherothrombosis, including platelets, endothelial cells, neutrophils and monocytes/macrophages (4-7). The remarkable clinical effects of low-dose aspirin in reducing the risk of stroke and myocardial infarction by 20 to 50% in various clinical settings (8) provide perhaps the most convincing evidence for the pathophysiologic importance of eicosanoid mechanisms in modulating the thrombotic outcome of plaque fissuring. That interference with a single mechanism of amplification of platelet activation, such as that provided by thromboxane (TX) A2-thromboxane receptor (TP) interactions on the platelet membrane, can lead to clinically detectable consequences is perhaps surprising, but certainly encouraging in the search of novel targets for pharmacological intervention.Considerable progress has been made in the eicosanoid field during the last ten years, well beyond the thromboxane/prostacyclin balance hypothesis (9), with the elucidation of at least three distinct modalities of eicosanoid biosynthesis, i.e., constitutive, inducible and transcellular. In this review, we shall discuss the molecular, cellular and pharmacological aspects of eicosanoid and iso-eicosanoid biosynthesis as they relate to the multifactorial process of atherothrombosis, with the aim of suggesting novel pathophysiologic mechanisms as well as potential therapeutic targets.